Unstable behavior of anodic arc discharge for synthesis of nanomaterials. (27th July 2016) - Gershman, Sophia; Raitses, Yevgeny
Abstract: A short carbon arc operating with a high ablation rate of the graphite anode exhibits a combined motion of the arc and the arc attachment to the anode. A characteristic time scale of this motion is in a 10 −3 s range. The arc exhibits a negative differential resistance before the arc motion occurs. Thermal processes in the arc plasma region interacting with the ablating anode are considered as possible causes of this unstable arc behavior. It is also hypothesized that the arc motion could potentially cause mixing of the various nanoparticles synthesized in the arc in the high ablation regime.